2004
DOI: 10.2139/ssrn.536563
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Promotion and GP Prescription Behaviour

Abstract: The aim of this paper is to empirically analyse the responses by general practitioners to promotional activities for pharmaceuticals by pharmaceutical companies. Promotion can be beneficial for society as a means of providing information, but it can also be harmful in the sense that it lowers price sensitivity of doctors and it merely is a means of establishing market share, even when cheaper, therapeutically equivalent drugs are available. A model is estimated that includes interactions of promotion expenditu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 8 publications
0
40
1
Order By: Relevance
“…In particular, marketing is said to reduce price sensitivity of demand for prescription drugs, leading to negative welfare effects. So, for example, Hurwitz and Caves (1988), Rizzo (1999), and Windmeijer et al (2005) find that marketing expenditures lower price sensitivity and conclude that marketing expenditures mainly have a persuasive effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, marketing is said to reduce price sensitivity of demand for prescription drugs, leading to negative welfare effects. So, for example, Hurwitz and Caves (1988), Rizzo (1999), and Windmeijer et al (2005) find that marketing expenditures lower price sensitivity and conclude that marketing expenditures mainly have a persuasive effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rizzo's (1999) model estimates the effects of promotional efforts on demand and the price elasticity of demand for antihypertensive drugs. In turn, Rizzo's model has been slightly modified in a study by Windmeijer et al (2005), which is based on De Laat et al (2002). Their study considers the following research questions: a.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, available literature on the impact of EPR is limited [41,48]. Evaluations focused on cost-containment, showing how EPR was able to contribute to savings under specific conditions [21,[58][59][60][61], whereas aspects such as availability and uptake have not been sufficiently addressed. One study showed that, using a limited sample of new patented medicines, EPR-applying countries had, in general, lower list prices than countries not using EPR [60].…”
Section: External Price Referencingmentioning
confidence: 99%
“…Despite the fact that they explore several costcontainment policies as explanatory variables (therapeutic value, cost-effectiveness, and so on), it is suggestive that the dummy variable for the presence of ER is the only explanatory variable that is significant at the 5% level. Windmeijer et al (2006) measure the effects of the implementation of ER in the Netherlands. They show that this policy resulted in considerably lower prices in general.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the works by Windmeijer et al (2006) and Heuer et al (2007) Unfortunately, more than exploring the effects of ER in isolation, most empirical studies aim at determining the effect of price controls in general. The empirical implication of our model (the effects of demand size, consumer copayment, and the separation of authorization and subsidization decisions) might serve as a guide for future empirical studies on the effects of ER as a cost control policy.…”
Section: Introductionmentioning
confidence: 99%